Introduction to Philosophy Philosophy of Religion - Branson, Beau; Hendricks, Christina (Open textbook library., 2020)
Introduction to Philosophy: Philosophy of Religion introduces some of the major traditional arguments for and against the existence of God, as well as some less well-known, but thought-provoking arguments for the existence of God, and one of the most important new challenges to religious belief from the Cognitive Science of Religion. An introductory chapter traces the connection between philosophy and religion throughout Western history, and a final chapter addresses the place of non-Western and non-monotheistic religions within contemporary philosophy of religion.